Evaluating the association of state regulation of community health workers on adoption of standard roles, skills, and qualities by employers in select states: a mixed methods study - Tammie M. Jones (BMC, 2021)
Abstract Background The occupation of community health worker (CHW) has evolved to support community member navigation of complex health and social systems. The U.S. Bureau of Labor Statistics formally recognized the occupation of community health worker (CHW) in 2009. Since then, various national and state efforts to professionalize the occupation have been undertaken. The Community Health Workers Core Consensus (C3) project released a set of CHW roles and competency recommendations meant to provide evidence-based standards for CHW roles across work settings. Some states have adopted the recommendations; however, there are a variety of approaches regarding the regulation of the occupation. As of 2020, 19 U.S. states have implemented voluntary statewide CHW certification programs. The purpose of this study was to explore the relationship between state regulation of CHWs and adoption of standard roles, skills, and qualities by employers in select states. Methods This mixed methods study used purposive sampling of job ads for CHWs posted by employers from 2017 to 2020 in select states. Natural language processing was used to extract content from job ads and preprocess the data for statistical analysis. ANOVA, chi-square analysis, and MANOVA was used to test hypotheses related to the relationship between state regulation of CHWs and differences in skills, roles, and qualities employers seek based on seniority of state regulatory processes and employer types. Results The mean job ads with nationally identified roles, skills, and qualities varies significantly by state policy type (F(2, 4801) = 26.21) and by employer type (F(4, 4799) = 69.08, p = 0.000). Conclusions Employment of CHWs is increasing to provide culturally competent care, address the social determinants of health, and improve access to health and social services for members of traditionally underserved communities. Employers in states with CHW certification programs were associated with greater adoption of occupational standards set by state and professional organizations. Wide adoption of such standards may improve recognition of the CHW workforce as a valuable resource in addressing the needs of high-need and marginalized groups.